DECONSTRUCTING PREJUDICES: CHALLENGES OF DISTANCE EDUCATION AND THE NEED FOR ACTIVE METHODOLOGIES (REMUNOM, 2025)
This article analyzes the challenges of distance education in the face of the need for active methodologies, focusing on the perspective of anti-racist education applied to the Judiciary of Pernambuco. The research used an online questionnaire as a methodological instrument, addressing the perception of employees regarding inclusive practices and racial equity policies. The results indicate low participation in anti-racist training, a widespread perception of insufficient institutional actions, and a strong demand for structural policies that promote diversity and inclusion. Anti-racist education, articulated with active methodologies, proves essential for promoting a more just and equitable environment, with a direct impact on professional practice and the administration of justice.